2008
DOI: 10.1182/blood-2008-01-133587
|View full text |Cite
|
Sign up to set email alerts
|

Etiologic heterogeneity among non-Hodgkin lymphoma subtypes

Abstract: Understanding patterns of etiologic commonality and heterogeneity for nonHodgkin lymphomas may illuminate lymphomagenesis. We present the first systematic comparison of risks by lymphoma subtype for a broad range of putative risk factors in a population-based case-control study, including diffuse large B-cell (DLBCL; N ‫؍‬ 416), follicular (N ‫؍‬ 318), and marginal zone lymphomas (N ‫؍‬ 106), and chronic lymphocytic leukemia/small lymphocytic lymphoma (CLL/ SLL; N ‫؍‬ 133). We required at least 2 of 3 analyses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
148
4
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 152 publications
(161 citation statements)
references
References 65 publications
6
148
4
3
Order By: Relevance
“…A recent study in classical HL patients has shown that despite the oncogenic effect of IGF‐IR, a higher expression at diagnosis predicted a favourable outcome both for overall survival and 5‐year progression‐free survival 19. In the current prospective study, the association between IGF‐I and overall lymphoma risk was close to significant; however, we had relatively limited sample size and lymphoma is a heterogeneous disease 20. Therefore, further prospective analyses of the association in studies with information on lymphoma subtype are warranted.…”
Section: Discussionmentioning
confidence: 81%
“…A recent study in classical HL patients has shown that despite the oncogenic effect of IGF‐IR, a higher expression at diagnosis predicted a favourable outcome both for overall survival and 5‐year progression‐free survival 19. In the current prospective study, the association between IGF‐I and overall lymphoma risk was close to significant; however, we had relatively limited sample size and lymphoma is a heterogeneous disease 20. Therefore, further prospective analyses of the association in studies with information on lymphoma subtype are warranted.…”
Section: Discussionmentioning
confidence: 81%
“…Although these data effectively characterize the subtype spectrum of lymphomas [18][19][20][21][22][23][24][26][27][28][29][30][31][32][33][34][35], most studies have excluded the majority of plasma cell neoplasms and leukemias (circulating phase). Therefore, these results may not be comparable with population-based incidence data for the entire spectrum of WHO classifications [10,42,43].…”
Section: Introductionmentioning
confidence: 74%
“…30,31 Epidemiologic studies discovered that immunodeficiency increased the probability of NHL. [31][32][33][34] Lymphocytes are mediators of antibody-dependent cell-mediated cytotoxicity 35 and are indicators of host immune activity. 17 Monocytes generate host antitumor immune suppression and play an important part in tumor angiogenesis, which promote cell proliferation and tumor invasion.…”
Section: Discussionmentioning
confidence: 99%